2001
DOI: 10.1038/modpathol.3880257
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Hybridization and Reverse Transcription–Polymerase Chain Reaction for Cyclin D1 mRNA in the Diagnosis of Mantle Cell Lymphoma in Paraffin-Embedded Tissues

Abstract: Mantle cell lymphoma (MCL) is characterized by the chromosomal translocation t(11;14), which involves rearrangement of the bcl-1 proto-oncogene to the immunoglobulin heavy chain gene and results in overexpression of cyclin D1 mRNA. In this study, we evaluated the diagnostic relevance of three methods that may be helpful in the diagnosis of MCL: in situ hybridization (ISH) and a stringent reverse transcriptase-polymerase chain reaction (RT-PCR) protocol for cyclin D1 mRNA, and immunohistochemistry for cyclin D1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
38
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 25 publications
7
38
0
Order By: Relevance
“…Others have used RT-PCR methods to assess for cyclin D1 in MCL with results in general agreement with our own (18,23,(25)(26)(27)(28). In some of these studies, the presence or absence of cyclin D1 was considered the endpoint without quantification (23).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Others have used RT-PCR methods to assess for cyclin D1 in MCL with results in general agreement with our own (18,23,(25)(26)(27)(28). In some of these studies, the presence or absence of cyclin D1 was considered the endpoint without quantification (23).…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies using Northern blot analysis, immunohistochemical methods, and semiquantitative RT-PCR methods have suggested that nonneoplastic lymphoid tissues are negative for cyclin D1 (4,18,23,24). However, it is clear from the data presented in this study that cyclin D1 mRNA is expressed at low levels in reactive lymphoid tissues when assessed using the real-time RT-PCR methods, as also has been described by others (25).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…It has been individualized both in the REAL and in the World Health Organization classifications because it represents a distinct clinical pathological entity with a special aggressive course among small B-cell lymphomas (2,3). It frequently involves lymph node, blood, bone marrow, and spleen (4,5). The neoplastic cells typically exhibit a centrocytic morphology and coexpress pan-B-cell markers CD5 and CD43 but lack CD23 and CD10.…”
mentioning
confidence: 99%